2008
DOI: 10.1242/dev.006718
|View full text |Cite
|
Sign up to set email alerts
|

P-cadherin is a p63 target gene with a crucial role in the developing human limb bud and hair follicle

Abstract: *P-cadherin is a member of the classical cadherin family that forms the transmembrane core of adherens junctions. Recently, mutations in the P-cadherin gene (CDH3) have been shown to cause two inherited diseases in humans: hypotrichosis with juvenile macular dystrophy (HJMD) and ectodermal dysplasia, ectrodactyly, macular dystrophy (EEM syndrome). The common features of both diseases are sparse hair and macular dystrophy of the retina, while only EEM syndrome shows the additional finding of split hand/foot mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 44 publications
3
120
0
Order By: Relevance
“…Importantly, the authors showed that p63 expression caused downregulation of cell adhesion-associated genes and detachment between mammary epithelial cells (Carroll et al, 2006). This involvement of p63 in cell adhesion mechanisms was finally linked with CDH3 gene, when Shimomura and colleagues demonstrated that P-cadherin is a direct p63 transcriptional target and that this interplay has a crucial role in human limb bud and hair follicle development (Shimomura et al, 2008) (Fig. 3).…”
Section: Recognized Regulators Of Cdh3/p-cadherin Transcriptionmentioning
confidence: 97%
See 1 more Smart Citation
“…Importantly, the authors showed that p63 expression caused downregulation of cell adhesion-associated genes and detachment between mammary epithelial cells (Carroll et al, 2006). This involvement of p63 in cell adhesion mechanisms was finally linked with CDH3 gene, when Shimomura and colleagues demonstrated that P-cadherin is a direct p63 transcriptional target and that this interplay has a crucial role in human limb bud and hair follicle development (Shimomura et al, 2008) (Fig. 3).…”
Section: Recognized Regulators Of Cdh3/p-cadherin Transcriptionmentioning
confidence: 97%
“…However, it is known that during bud patterning, a special arrangement occurs, where cells change their interaction with their neighbours and break their attachments to the extracellular matrix (ECM). Cells achieve this by activating specific transcriptional programs (Shimomura et al, 2008).…”
Section: B Amentioning
confidence: 99%
“…30,31 Moreover, many genes, including SHFM diseasecausing genes such as TP63 and WNT10b, are expressed in this region. 32,33 DLX5 and DLX6 are very similar in that, both are candidate genes for SHFM1, tandemly arranged on locus 7q21 tail to tail and are expressed in the median AER of embryonic limb buds. Simultaneous knockout of DLX5 and DLX6 in the mouse results in the SHFM phenotype.…”
Section: Dlx5 Mutation Causes Shfm1mentioning
confidence: 99%
“…Four genes that were previously shown to be elevated in WT mice but not in p63-null mice at E14.5 (GJA1, GJ6B, KRT14, KRTDAP) (19) were rescued by APR-246. Moreover, the level of expression of three p63-target genes (DLX5, DLX6, and CDH3/P-Cadherin) that are known to be associated with EEC syndrome (20,21) was significantly enhanced by APR-246. Interestingly, we found that APR-246 acted differently on the R204W and R304W mutants.…”
Section: δNp63mentioning
confidence: 99%